Constrained Wiki: The WikiWay to Validating Content. (19th April 2012) - Di Iorio, Angelo; Draicchio, Francesco; Vitali, Fabio; Zacchiroli, Stefano
Abstract : The "WikiWay" is the open editing philosophy of wikis meant to foster open collaboration and continuous improvement of their content. Just like other online communities, wikis often introduce and enforce conventions, constraints, and rules for their content, but do so in a considerably softer way, expecting authors to deliver content that satisfies the conventions and the constraints, or, failing that, having volunteers of the community, the WikiGnomes, fix others' content accordingly. Constrained wikis is our generic framework for wikis to implement validators of community-specific constraints and conventions that preserve the WikiWay and their open collaboration features. To this end, specific requirements need to be observed by validators and a specific software architecture can be used for their implementation, that is, as independent functions (implemented as internal modules or external services) used in a nonintrusive way. Two separate proof-of-concept validators have been implemented for MediaWiki and MoinMoin, respectively, providing an annotated view functions, that is, presenting content authors with violation warnings, rather than preventing them from saving a noncompliant text.